دور البرامج الدينية الناطقة باللغة الفرنسية في نشر القيم الإسلامية - دراسة ميدانية على عينة من متابعي برنامج " تأملات - "réfléxionلكمال شكات في قناة القرآن الكريم - بغورة تينهينان (جامعة محمد بوضياف – مسيلة, 2025)
This study aims to explore the role of French-language religious programs in promoting Islamic values, through a field study of the audience of the program “Réflexion” by Kamal Chikkat, broadcast on the Quran TV Channel. The study adopts the descriptive survey method and is based on the Uses and Gratifications Theory. Data were collected through a questionnaire divided into five main sections and comprising 21 questions. It was distributed to a purposive sample of 40 individuals who follow the program. The study reached several key findings, most notably: • The program “Réflexion” enjoys significant viewership among youth and women, reflecting the appeal of religious content to these demographic groups. • The program effectively contributes to promoting Islamic values by presenting them in simplified French, making it accessible to non-Arabic speakers. • YouTube emerged as the primary platform for following the program, with a preference for individual viewing that enhances personal connection with the content. تهدف هذه الدراسة إلى معرفة دور البرامج الدينية الناطقة باللغة الفرنسية في نشر القيم الإسلامية، من خلال دراسة ميدانية على متابعي برنامج " تأملات - "réflexionلكمال شكات في قناة القرآن الكريم. تم الاعتماد على المنهج الوصفي المسحي مع الاعتماد على نظرية الاستخدامات والإشباعات. وتم جمع البيانات باستخدام الإستبيان وقسم إلى خمسة محاور رئيسة وتضمن 21سؤال، ووزع على عينة قصدية مكونة من 40مفردة من متابعي البرنامج، وتوصلت هذه الدراسة إلى مجموعة من النتائج أهمها: - برنامج" تأملات " يحظى بمتابعة قوية من الشباب والنساء، مما يعكس جاذبية المجموعات المهتمة بالمضمون الديني. - يسهم البرنامج بفعالية في نشر القيم الإسلامية وتقديمها بلغة فرنسية مبسطة تناسب جمهور غير الناطقين بالعربية. - يبرز استخدام اليوتيوب كوسيلة رئيسية لمتابعة البرنامج، مع تفضيل المشاهدة الفردية التي تعزز التواصل الشخصي مع المحتوى